An appetite for risk? Failure to replicate the effect of hunger cues on risk taking. (September 2018) - Festjens, Anouk; Bruyneel, Sabrina; Dewitte, Siegfried
Highlights: Ditto et al. (2006) found that external hunger cues decrease sensitivity to risk information. This is cited as if hunger increases risk-taking. We test whether external versus internal hunger cues influence risk-taking. We find no main effect of external hunger cues, but an interaction effect of both cues on risk-taking. Abstract: Ditto et al. (2006) reported that consumers who are exposed to external hunger cues (i.e., scent of freshly baked cookies) are less sensitive to risk information. That is, consumers exposed to hunger cues are as likely to take risks in situations with a high versus low probability of losing. Yet, this result is often cited as evidence that hunger increases risk-taking. This may be due to the fact that Ditto et al. (2006) observed that hunger cues increased risk-taking in situations with a high chance of losing. We attempted to replicate this specific contrast in two studies. In the first study, the risk measure was in the food domain (like in Ditto et al., 2006) and in the second study it was in the financial domain. Yet, we failed to observe a main effect of exposure to external food cues on risk-taking. In addition, as it is an untested assumption in the literature that external (cookie scent) versus internal (not eating for several hours) hunger cues can be used interchangeably, we also checked for a potential moderation by type of hunger cue. We did not observe such a moderation when the risk task involved food outcomes, but we detect such an effect when it involved financial outcomes. These results suggest that the widely held assumptions that (1) hunger or exposure to hunger cues induce risk taking and that (2) internal and external hunger cues are exchangeable should be revisited.